Therapeutic, phytochemistry, and pharmacology of acorns (Quercus Nuts): a review - Ferreira da Vinha, Ana (2020)
The current global food system must adapt to the expected growth of world population. This adaptation will probably include an increased consumption of edible wild foods, due to their richness in micronutrients and bioactive compounds, besides providing a cost-effective and sustainable way of improving caloric food security. Acorns (Quercus nuts) have been presenting an important role on the rural economy. In fact, their nutritional value; high contents in bioactive compounds; biological activity such as antioxidant, anticarcinogenic, and cardioprotective properties; and use in the treatment of specific diseases such as atherosclerosis, diabetes, or Alzheimer’s disease have raised the interest in integrating acorns into the human diet. In the present review, we present the chemical constituents of acorns and their biological activities.